Internalization-Dependent and -Independent Requirements for Transforming Growth Factor β Receptor Signaling via the Smad Pathway - Penheiter, Sumedha G. (American Society for Microbiology, 2002)
Members of the transforming growth factor β (TGF-β) family of proteins signal through cell surface transmembrane serine/threonine protein kinases known as type I and type II receptors. The TGF-β signal is extended through phosphorylation of receptor-associated Smad proteins by the type I receptor. Although numerous investigations have established the sequence of events in TGF-β receptor (TGF-βR) activation, none have examined the role of the endocytic pathway in initiation and/or maintenance of the signaling response. In this study we investigated whether TGF-βR internalization modulates type I receptor activation, the formation of a functional receptor/Smad/SARA complex, Smad2/3 phosphorylation or nuclear translocation, and TGF-β-dependent reporter gene activity. Our data provide evidence that, whereas type I receptor phosphorylation and association of SARA and Smad2 with the TGF-βR complex take place independently of clathrin lattice formation, Smad2 or Smad3 activation and downstream signaling only occur after endocytic vesicle formation. Thus, TGF-βR endocytosis is not simply a way to dampen the signaling response but instead is required to propagate signaling via the Smad pathway.